THE SITUATION OF THE STRANGER IN LIQUID MODERNITY: THE PROCESS OF BECOMING NOBODY - Doğa BAŞER (Fırat University, 2019)
Zygmunt Bauman is known with his critical works towards our contemporary world. In this study, Bauman’s typology of stranger is evaluated through periodization of liquid modernity. In Bauman’s works, stranger is described as a person, who is physically close and mentally distant, encountered in our social life. . Liquid modernity, on the other hand, refers to societies’ flexible, fragile and in